Evaluation of forces on muscles and intervertebral joints during active kyphosis-deepening exercises in the dynamic individual stimulation and control for spine device (DISC4SPINE, D4S): a modeling approach—proof of concept study - Szurmik, Tomasz; Bibrowicz, Karol; Nowakowska-Lipiec, Katarzyna; Zadoń, Hanna; Michnik, Robert; Mitas, Andrzej Waldemar (Frontiers in Sports and Active Living, 2025)
IntroductionIn the conservative treatment of scoliosis, it is important to monitor the response of the muscles and the forces acting on the intervertebral joints during the recommended therapy. This study aimed to evaluate the forces exerted by the limbs and intervertebral joints, as well as the forces of selected muscles on both sides of the back, during active spinal kyphosis exercises in the supported kneeling position used in the PRESSIO method.MethodsAn experimental biomechanical investigation was conducted using a prototype of the DISC4SPINE system. One healthy subject was examined. During the exercise, contact forces acting on the surfaces of the hands and knees, as well as forces generated by the system's resistance elements acting on the subject's body, were recorded. The kinematic parameters of the movement were documented using a video camera. The collected measurement data was used to inform simulations conducted within the ANYBODY modelling system environment, employing the FreePosture whole-body model. Two positions were modelled: position 0 represented the resting state with no exercise or active interaction with the system's heads, and position 1 represented kyphotic movements of the spine with simultaneous interaction with the system's resistance elements.ResultsThe simulation results showed a significant increase in mean force values acting on the upper and lower extremities in the active kyphotic position compared to position 0.DiscussionThe supported kneeling position employed in the PRESSIO method is characterised by reduced force exerted along the long axis of the spine, creating favourable conditions for correction. An increase in the average values of intervertebral forces was also observed in position 1 compared to position 0. Furthermore, active kyphosis of the spine caused an increase in muscle activity in the back extensor muscles (Erector Spinae, ES).